Speaking anxiety among ESL learners in the Malaysian classroom / Hazwati Hashim - Hashim, Hazwati (Academy of Language Studies, Universiti Teknologi MARA Negeri Sembilan Branch, Rembau Campus, 2024)
The challenges ESL learners face in speaking English in Malaysian classrooms are influenced by various factors. These challenges include speaking anxiety, lack of self-confidence, nervousness, inhibition, vocabulary limitations, and communication apprehension (Nijat et al., 2019; Yahaya et al., 2021; Bayuong et al., 2019). ESL learners often struggle with selfconfidence, fear of negative evaluation, shyness, and worry about making mistakes, which impede their speaking skills (Nijat et al., 2019). Additionally, task-based approaches, psychological factors, and language learning strategies are crucial in addressing these challenges (Yahaya et al., 2021; Bayuong et al., 2019).